Overview on the degradability of polymer nanocomposites - Pandey, JK; Reddy, KR; Kumar, AP; Singh, RP (Polymer Degradation and Stability, 2005)
Polymer nanocomposites have attracted great attention world wide from both academic and industrial points of view. The material properties of polymers can be enhanced dramatically by incorporating layered silicates at fairly low concentrations. The durability of any material depends upon several factors e.g. light, heat, microwaves, mechanical abrasion etc. The study and the effect of these factors on the performance are essentially required to extend the application limits. The durability of polymer nanocomposites has been evaluated under different environments. The present review describes the durability of different polymer nanocomposites mainly under thermal- and photoageing. Biodegradable nanoeomposites of different polymers are also discussed briefly. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: Biodegradation; Degradation; layered silicates; Nanocomposites; weathering